O‘ZBEKISTON OLIY TA’LIM MUASSASALARIDA RAQAMLI BRENDNI SHAKLLANTIRISHDA IJTIMOIY TARMOQLARNING TA’SIRI - Xakimov Ziyodulla Axmadovich; Xidoyatov Murod Batirovich (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article analyzes the role and effectiveness of social networks in shaping digital branding in higher education institutions of Uzbekistan. The study examines the growth of internet and social media users, the digital communication strategies of universities, and the use of content marketing tools to strengthen institutional brand image. The activity of leading universities such as TDIU, WIUT, IUT, TATU, and TTPU on social media is compared to identify best practices for effective digital branding. The conclusion highlights the central role of social media within the digital marketing ecosystem and its strategic importance for universities in enhancing their reputation and student engagement.